1992
DOI: 10.1130/0091-7613(1992)020<0697:pidatc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Proximal impact deposits at the Cretaceous-Tertiary boundary in the Gulf of Mexico: A restudy of DSDP Leg 77 Sites 536 and 540

Abstract: Restudy of Deep Sea Drilling Project Sites 536 and 540 in the southeast Gulf of Mexico gives evidence for a giant wave at Cretaceous-Tertiary boundary time. Five units are recognized: (1) Cenomanian limestone underlies a hiatus in which the five highest Cretaceous stages are missing, possibly because of catastrophic K-T erosion. (2) Pebbly mudstone, 45 m thick, represents a submarine landslide possibly of K-T age. (3) Current-bedded sandstone, more than 2.5 m thick, contains anomalous iridium, tektite glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 1 publication
3
74
0
Order By: Relevance
“…They found that the impact-glass particles at these marine sites are partly altered to smectite. We feel that the glass particles discovered by Alvarez et al (1992) are probably similar to those originally deposited in the K/T lower claystone layer but were subsequently altered to mostly kaolin minerals in the ancient peat swamp.…”
Section: Comparison O F K / T Boundary Unit To Tonsteins and Detritalmentioning
confidence: 93%
See 1 more Smart Citation
“…They found that the impact-glass particles at these marine sites are partly altered to smectite. We feel that the glass particles discovered by Alvarez et al (1992) are probably similar to those originally deposited in the K/T lower claystone layer but were subsequently altered to mostly kaolin minerals in the ancient peat swamp.…”
Section: Comparison O F K / T Boundary Unit To Tonsteins and Detritalmentioning
confidence: 93%
“…Specifically, the K/T lower claystone layer contains mostly homogeneous types ofneoformed clay minerals, little quartz and feldspar, and no detrital illite or muscovite: a mineral assemblage very similar to those that make up altered, vitric, volcanic ash-fall beds and tufts (Minato and Utada, 1969;Schultz, 1978;Hoffman and Hower, 1979;Sudo et al, 1981;Bohor et aL, 1978;Pollastro and Scholle, 1986) and strongly implies a glass precursor for the KiT boundary layers. Furthermore, Alvarez et al (1992) recently discovered several fragments of impact-ejecta glass stringers, shards, droplets, and spherules preserved at the K/T boundary in DSDP Leg 77, Sites 536 and 540, southeast Gulf of Mexico. They found that the impact-glass particles at these marine sites are partly altered to smectite.…”
Section: Comparison O F K / T Boundary Unit To Tonsteins and Detritalmentioning
confidence: 99%
“…Haiti and Mimbral, as well as gravity measurements and drill core data that imply the existence of a 180 km diameter structure of Maastrichtian-earliest Paleocene age beneath the Yucatan (Sigurdsson et al, 1991b;Margolis et al, 1991;Alvarez et al, 1991;Hildebrand and Boynton, 1990). Re-analysis of DSDP Sites 536 and 540 in the Gulf of Mexico has led to the discovery of thick deposits of reworked carbonates of diverse ages.…”
Section: The Cretaceous-paleocene Meteorite Eventmentioning
confidence: 99%
“…These deposits contain uppermost Maastrichtian nannofossils and occur immediately below lowermost Paleocene sediments. Alvarez et al (1991) have interpreted these K/P boundary deposits as part of the ejecta blanket. Size distributions of spherules found in boundary beds on Haiti and in the DSDP sites indicate that the impact occurred within the Caribbean (Sigurdsson et al, 1991ba).…”
Section: The Cretaceous-paleocene Meteorite Eventmentioning
confidence: 99%
“…200 m , Sharpton et al, 1996;Pierazzo et al, 1998Bougeois et al, 1988Alvarez et al, 1992;Smit et al, 1992Smit et al, , 1996Smit, 1999;Takayama et al, 2000;Matsui et al, 2002;Tada et al, 200240 K/T 1990Smit et al, 1992, 1996Keller et al, 1993Keller et al, , 1997Keller et al, , 2002aSmit, 1999;Soria et al, 2001 K/T 1 3 m Fig. 2; Smit et al, 1992 1 Fig.…”
mentioning
confidence: 99%